Strengthening Social Capital in Increasing The Welfare of Members in The Gapoktan Tani Makmur, Ngawi Regency - Khoiriyati, Roisatul; Winarno, Joko; Lestari, Eny (CV. Publikasi Indonesia, 2022)
The agricultural sector is an important sector as a provider of food for food tenacity. Food tenacity can be achieved by optimizing agricultural development by investing social capital, physical capital, human capital, and financial capital. Communities that have high social capital will tend to be more efficient and effective in carrying out various policies to prosper and advance the lives of their members. This research aims to identify social capital, factors that affect social capital, and provide strengthening of social capital. Qualitative descriptive method was applied by using primary and secondary data. Primary data obtained from interviews with 10 respondents who joined Gapoktan Tani Makmur while the secondary data taken from some literature and related agencies. The results showed that social capital in Kartoharjo Village can be seen from the trust between Gapoktan members as evidenced by the existence of RAT every year, reciprocity is shown by the collaboration between PT WPI and Gapoktan, values and norms can be found when facing problems, the resolution is through deliberation, the commitment of members trying to carry out their duties with full responsibility, and also the proactive attitude of Gapoktan shown in meeting the needs of farmers continues to be improved. External factors that affect social capital such as PT Wilmar Padi Indonesia, NGOs, and the government. Internal factors that affect social capital are high motivation, and the commitment of the management and members of Gapoktan. Strengthening Social Capital Gapoktan Tani Makmur can be done by strengthening self-capacity both in business effort and management regeneration.